Usefulness of optical enhancement endoscopy combined with magnification to improve detection of intestinal metaplasia in the stomach - Sobrino-Cossío, Sergio; Teramoto-Matsubara, Oscar; Emura, Fabian; Araya, Raúl; Arantes, Vítor; Galvis-García, Elymir S.; Meza-Caballero, Marisi; García-Aguilar, Blanca Sinahi; Reding-Bernal, Arturo; Uedo, Noriya (Endoscopy International Open, 2022)
Background and study aims The light blue crest observed in narrow band imaging endoscopy has high diagnostic accuracy for diagnosis of gastric intestinal metaplasia (GIM). The objective of this prospective study was to evaluate the diagnostic accuracy of magnifying i-scan optical enhancement (OE) imaging for diagnosing the LBC sign in patients with different levels of risk for gastric cancer in a Mexican clinical practice.Patients and methods Patients with a history of peptic ulcer and symptoms of dyspepsia or gastroesophageal reflux disease were enrolled. Diagnosis of GIM was made at the predetermined anatomical location and white light endoscopy and i-scan OE Mode 1 were captured at the two predetermined biopsy sites (antrum and pyloric regions).Results A total of 328 patients were enrolled in this study. Overall GIM prevalence was 33.8 %. The GIM distribution was 95.4 % in the antrum and 40.5 % in the corpus. According to the Operative Link on Gastritis/Intestinal-Metaplasia Assessment staging system, only two patients (1.9 %) were classified with high-risk stage disease. Sensitivity, specificity, positive​ and negative predictive values, positive and negative likelihood ratios, and accuracy of both methods (95 % C. I.) were 0.50 (0.41–0.60), 0.55 (0.48–0.62), 0.36 (0.31–0.42), 0.68 (0.63–0.73), 1.12 (0.9–1.4), 0.9 (0.7–1.1), and 0.53 (0.43–0.60) for WLE, and 0.96 (0.90–0.99), 0.91 (0.86–0.94), 0.84 (0.78–0.89), 0.98 (0.94–0.99), 10.4 (6.8–16), 0.05 (0.02–0.12), and 0.93 (0.89–0.95), respectively. The kappa concordance was 0.67 and the reliability coefficient was 0.7407 for interobserver variability.Conclusions Our study demonstrated the high performance of magnifying i-scan OE imaging for endoscopic diagnosis of GIM in Mexican patients.